STUDY OF SUBSISTENCE FARMING COMMUNITY IN NORTH LINTAU BUO JORONG KAYU MERANTING - SABABALAT, DARNITA; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd; Despica, S.Pd., M.Si, Rika (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This study aims to obtain data , information and description of the Plant Patchouli (Pogostemon cablin Benth) in Makalo village Pagai Selatan District Mentawai Islands Region seen from: 1) the maintenance and care and 2) marketing.This type of research is descriptive. Population of all farmers in the village of patchouli in Makalo villageare 568 households. Samples were taken with a proportional random sampling technique with the proportion of 15% so that the sample was 84 farmers.The results of the study found : 1 ) Patchouli crop management techniques in Makalo village Mentawai Islands Region, farmer doing embroidery at age < 1 month until the age of 3 months, conducted during the morning and afternoon. Fertilization patchouli farmers in Makalo villade generally use NPK fertilizers and performed at the age of 1 month after planting. For the first weeding patchouli performed at the age of 1 month and weeding done 3 times. While farmers in the Makalo village generally never do and 2) Marketing patchouli plants generally use system sales by an estimated per kg of oil and the buyer is a big toke and some are directly sold to the market. Constraints patchouli farmers in Makalo village Pagai Selatan District Mentawai Islands Region in transport due to the Makalo transportati system is not smooth and more farmers using a speed boat in the sale and issue onof transport costs are expensive. Frequency selling patchouli oil generally uncertain. Results of patchouli oil obtained by farmers in the last one year depending on the weather and the land area. In 1 year, farmers usually harvest 4 times and average the results obtained in 1 Ha patchouli ranged from 5-10 kg